Defining informative priors for ensemble modeling in systems biology. Issue 11 (November 2018) - Tsigkinopoulou, Areti; Hawari, Aliah; Uttley, Megan; Breitling, Rainer
Abstract Ensemble modeling in molecular systems biology requires the reproducible translation of kinetic parameter data into informative probability distributions (priors), as well as approaches that sample parameters from these distributions without violating the thermodynamic consistency of the overall model. Although a number of pioneering frameworks for ensemble modeling have been published, the issue of generating informative priors has not yet been addressed. Here, we present a protocol that aims to fill this gap. This protocol discusses the collection of parameter values from a diverse range of sources (literature, databases and experiments), assessment of their plausibility, and creation of log-normal probability distributions that can be used as informative priors in ensemble modeling. Furthermore, the protocol enables sampling from the generated distributions while maintaining thermodynamic consistency. Once all parameter values have been retrieved from literature and databases, the protocol can be implemented within ~5–10 min per parameter. The aim of this protocol is to facilitate the design and use of informative distributions for ensemble modeling, especially in fields such as synthetic biology and systems medicine. This protocol addresses the need to define informative priors to apply ensemble modeling in systems biology. The protocol collects parameters, assesses their plausibility and creates log-normal probability distributions for use as informative priors.